Utilizing Location Quotient (LQ) and Shift-Share (SS) Techniques to Analyze Key Industries in Yogyakarta City - Azra, Kurniawan; Yaseen, Atif (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
The current era of regional autonomy has led to an increased complexity in regional development and heightened competition among regions. To achieve sustainable development in each regency and city, particularly in the Special Region of Yogyakarta, the Provincial Government of DIY has allocated special funds to improve the welfare of the community. Analyzing the leading industries in Yogyakarta is the objective of this research. Secondary data for this research were obtained through the official websites of the Central Statistics Agency (BPS) of DIY Province and BPS of Yogyakarta City. Using the shift share and location quotient analysis techniques, this research is of a quantitative descriptive nature. Based on the research findings, the leading sectors in Yogyakarta from 2018 to 2022 have been identified, comprising a total of 11 fields or sectors: (1) Manufacturing Industry; (2) Gas and Electricity Provision; (3) Water Supply; (4) Waste Processing; (5) Information and Communication; (6) Financial and Insurance Services; (7) Real Estate; (8) Corporate Services; (9) Government Administration; Defense and Mandatory Social Security; (10) Education Services; (11) Health and Social Activities. In the other hand, only the health and social activities sector is deemed most suitable (primary priority) for continuous sustenance and development.